Development of energy safety features traffic flow - Дудніков, Олександр Миколайович; Дуднікова, Наталя Миколаївна (Eastern-European Journal of Enterprise Technologies, 2013)
The article examines an actual scientific problem of traffic safety. Among the range of tasks that determine the issue attention is paid to the development of the determined energy characteristic of traffic safety on the basis of application of the law of conservation and transformation of mechanical energy and its experimental justification. The results permit to formulate additionally determined principle of formation of the heaviness of the accident - the current traffic safety as an estimated heaviness of the accident on a particular area of road is directly proportional to the cube of velocity of flow of corresponding number of cars and mass density of traffic flow moving on it. From a practical point of view justified dependences permitted to perform direct calculations of the maximum and expected heaviness of the accident on specific areas of the road, to change the expected heaviness by the corresponding cubic decrease of traffic speed or by proportional change of mass density of the flow (recommending the optimal distance between cars). Optionally, it becomes possible to maintain the expected heaviness of traffic accidents by increasing traffic speed by means of reduction of the cubic mass density of traffic flow